CIRI-CIRI KEPEMIMPINAN PEDESAAN YANG DAPAT MENDORONG DAN MEMPERTAHANKAH PERAN-SERTA MASYARAKAT DALAM KEGIATAN PENIMBANGAN : PERSEPSI KADER POSYANDU PEDESAAN DI KECAMATAN MLONGGO KABUPATEN JEPARA - Widagdo, Laksmono (JURNAL BISNIS STRATEGI, 2007)
The weighing activities in the integrated health and family planning services (Posyandu) forms one of the community based health efforts and is a strategy to ensure child survival as well as their mental and physical development and protectfon. Secondary research indicates that community participation cannot rise by itself and that it must by continuously motivated by other parties. These include the government and non-government organizations, as well as from within the communities. Motivations from government and non-govemment organizations are often temporary, while motivations from the community are often expected to be sustainable. In its implementation, however, the weighing activities often face many impediments and failures, though some have been successfui. One of the main failures is reflected in the drop-out rates of the village kader due to the lack of motivation especially from the village heads (kades). The qualitative research was done in stages focusing on characteristics of leadership, while a quantitative analysis through a cross sectional su vey was done to show the significance of such leadership. The results both qualitative and quantitative analysis shows a relation between leadership and kaders attitude and a relation between leadership and the achievement of the weighing activities program in posyandu significantly. It means that drop-out rates of kaders are indeed affected by kades leadership which also affects the overall performance including the weighing activities.